Short Communication: Cytological studies on black orchid hybrid (Coelogyne pandurata Lindley) - SRI HARTATI; NANDARIYAH NANDARIYAH; AHMAD YUNUS; DJATI W. DJOAR (Biodiversitas Journal of Biological Diversity, 2017)
Hartati S, Nandariyah, Yunus A, Djoar DW. 2017. Cytological studies on black orchid hybrid (Coelogyne pandurata Lindley). Biodiversitas 18: 555-559. Black orchid (Coelogyne pandurata Lindley) is one of the rare species of Coelogyne Lindley, protected by the government of Indonesia. The cytological character of orchid is very important to study to support the success of breeding. The study aimed to assess the chromosomal number, karyotype pattern and ploidy level the hybrid of Black Orchid (Coelogyne pandurata). This study shows that the chromosomal number of the hybrid of Coelogyne pandurata (2n = 36) >< Coelogyne rumphii (2n = 72) is 2n = 54. Ploidy analysis by flow cytometry shows that hybrid shows triploid (2n = 3x = 54) different from the parent Coelogyne pandurata which is diploid (2n = 2x = 36) and the parent Coelogyne rumphii which is tetraploid (2n = 4x = 72). However, both parents and their hybrid performed the same karyotype pattern, which is metacentric. The chromosome size showed a variation in length from the longest Coelogyne pandurata 2.98 ± 0.15 µm to the shortest Coelogyne rumphii 2.24 ± 0.15 µm. The hybrids have a range of 2.50 ± 0,10 µm to 2.85 ± 0.10 µm. Karyotype patterns of black orchid (C. pandurata), C. rumphii and the hybridis metacentric.